2023
DOI: 10.1021/acsphyschemau.3c00008
|View full text |Cite
|
Sign up to set email alerts
|

Delta SARS-CoV-2 s2m Structure, Dynamics, and Entropy: Consequences of the G15U Mutation

Abstract: Bioinformatic analysis of the Delta SARS-CoV-2 genome reveals a single nucleotide mutation (G15U) in the stem-loop II motif (s2m) relative to ancestral SARS-CoV-2. Despite sequence similarity, unexpected differences between SARS-CoV-2 and Delta SARS-CoV-2 s2m homodimerization experiments require the discovery of unknown structural and thermodynamic changes necessary to rationalize the data. Using our reported SARS-CoV-2 s2m model, we induced the G15U substitution and performed 3.5 microseconds of unbiased mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
2
1
0
Order By: Relevance
“…A difference in kissing dimer conformation is more probable as the monomers of these two s2m elements have a different shape based on their different migration in the TBM gel (Figure 6 right, arrows 1 and 1'). Moreover, our MD simulation findings show that the monomer s2m G15U is linear, while the original s2m monomer is kinked; this is consistent with this hypothesis (Makowski et al 2023). Despite these observed differences in the s2m G15U kissing dimer versus the s2m reference kissing dimer, we further demonstrate that this mutation does not affect the ability of the viral N protein to convert the s2m G15U kissing dimer to a stable duplex structure, which is the in vivo process of duplex formation.…”
Section: Characterization Of the Sars-cov-2 S2m G15u Dimerizationsupporting
confidence: 86%
See 1 more Smart Citation
“…A difference in kissing dimer conformation is more probable as the monomers of these two s2m elements have a different shape based on their different migration in the TBM gel (Figure 6 right, arrows 1 and 1'). Moreover, our MD simulation findings show that the monomer s2m G15U is linear, while the original s2m monomer is kinked; this is consistent with this hypothesis (Makowski et al 2023). Despite these observed differences in the s2m G15U kissing dimer versus the s2m reference kissing dimer, we further demonstrate that this mutation does not affect the ability of the viral N protein to convert the s2m G15U kissing dimer to a stable duplex structure, which is the in vivo process of duplex formation.…”
Section: Characterization Of the Sars-cov-2 S2m G15u Dimerizationsupporting
confidence: 86%
“…Similarly, it is interesting to note that, despite having the same size, the monomer bands for the s2m reference and s2m G15U migrate differently in the TBM gel (Figure 6, right, arrow 1 and 1'), suggesting that they have different monomer conformations in the presence of MgCl 2 . Our MD simulations for the s2m revealed that it has a kinked 3D structure; however, the additional U15-A29 base pair in the upper stem of s2m G15U results in a linear structure that lacks the L-shaped kink, rationalizing the increased migration of s2m G15U through the TBM gel as compared to the original s2m form (Kensinger et al 2022;Makowski et al 2023). Thus, we cannot determine if the single dimer band observed for the s2m G15U in the TBM gel (Figure 6, right, arrow 3) originates from a mixture of linear kissing dimer and duplex conformations which will migrate at the same position, or from the duplex conformation formed spontaneously from an unstable kissing dimer during incubation and migration through the gel (Shetty et al 2010).…”
Section: Characterization Of the Sars-cov-2 S2m G15u Dimerizationmentioning
confidence: 80%
“…These ambiguities, however, do not lead to a wrong secondary structure. In fact, followup MD simulations are in agreement with our dynamic NMR data (Makowski et al 2023).…”
Section: Discussionsupporting
confidence: 88%